A primer on the 35-hour in France, 1997 - 2007 - Philippe Askenazy (Institute for the Study of Labor (IZA), 2008)
France has experienced massive changes in its regulation of working time during the last decade. These changes generate natural experiments that may help to study a variety of issues in labor economics, including work sharing effect on job creation or productivity, labor relations or adaptation of firms to regulation. This paper provides a primer for researchers interested by working on these issues. It includes detailed information about the 35-hour laws and their progressive removal, and discusses the first wave of research evaluating these policies, that draws a contrasted picture. It also highlights some unexplored lines of research.
urn:nbn:de:101:1-2008032047
Keywords: J20; 330; France; 35-hour week; working time; bargaining; Arbeitszeitflexibilisierung; Wirkungsanalyse; Arbeitszeit; Beschäftigungseffekt; Produktivität; Arbeitsbeziehungen; Wirtschaftliche Anpassung; Frankreich